Internal training load affects day-after-pretraining perceived fatigue in female volleyball players - Ungureanu, A. N.; Lupo, C.; Boccia, G.; Brustio, P. R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The primary aim of this study was to evaluate whether the internal (session rating of perceived exertion [sRPE] and Edwards heart-rate-based method) and external training load (jumps) affect the presession well-being perception on the day after (ie, +22 h), according to age and tactical position, in elite (ie, Serie A2) female volleyball training.